La Biennale di Venezia - Settore Arti Visive '80 : Catalogo generale 1980. - La Biennale di Venezia, 1980 (Venezia : La Biennale di Venezia, 1980)
Magdalena Abakanowicz ; Vito Acconci ; Carl Andre ; Richard Artschwager ; Balthus ; Georg Baselitz ; Joseph Beuys ; Christian Boltanski ; Marcel Broodthaers ; Daniel Buren ; Sandro Chia ; Christo ; Tony Cragg ; Enzo Cucchi ; Dadamaino ; Jan Dibbets ; Ger van Elk ; Barry Flanagan ; Gilbert & George ; Roni Horn ; Jörg Immendorff ; Donald Judd ; Anselm Kiefer ; Jannis Kounellis ; Richard Long ; Markus Lüpertz ; Ingeborg Lüscher ; Walter De Maria ; Mario Merz ; Robert Morris ; Bruce Nauman ; Anna Oppermann ; Gerhard Richter ; Reiner Ruthenbeck ; Richard Serra ; Hubert Schmalix ; Keith Sonnier ; Frank Stella ; Cy Twombly ; etc.
2 ex. : 1 ex.: Italiaanse tekst (261 p.), 1 ex.: Engelse tekst (267 p.)
La biennale di Venezia, 01.06 - 28.09.1980
Engels & Italiaans
kunstcatalogus